Identifikasi Makroskopis, Mikroskopis, Dan Skrining Fitokimia Bunga Telang (Clitoria ternatea, L.) Varian Biru Dan Ungu Muda - Lingir Huar, Salestina; Rumaseuw, Ellen Stephanie (JURNAL FARMASI GALENIKA, 2025)
Butterfly pea flower (Clitoria ternatea, L.) is a medicinal plant known for its pharmacological properties due to the presence of various bioactive compounds. This study aims to identify the macroscopic, microscopic, and phytochemical characteristics of the blue and light purple variants of butterfly pea flowers cultivated in Cipangeran Village, Saguling District, West Bandung Regency. The research employed a descriptive qualitative method with an experimental approach. Macroscopic identification was conducted by observing the color, shape, odor, and texture of the flowers, while microscopic observation was performed using powdered simplicia preparations under a microscope finding indentifier fragmen. Phytochemical screening was conducted using specific reagents to detect the presence of secondary metabolites such as alkaloids, flavonoids, saponins, steroids/triterpenoids, and tannins. The results showed that both flower variants have morphological features typical of the Fabaceae family, with distinct color gradients and varied textures. Microscopic analysis revealed identifying fragments such as sclerenchyma, pollen grains, vascular bundles, covering trichomes, collenchyma, and idioblasts containing oil cells. Phytochemical screening indicated the presence of flavonoids, steroids/triterpenoids, tannins, and alkaloids in both variants. Saponins were detected only in the blue variant. These findings suggest that both blue and light purple butterfly pea flower variants have potential as raw materials for herbal health products.